Prenatal development of skull and brain in a mouse model of growth restriction - Barbeito Andrés, Jimena (2016)
Patterns of covariation result from the over-lapping effect of several developmental processes. By perturbing certain specific developmental processes, ex-perimental studies contribute to a better understanding of their particular effects on the generation of phenotype. The aim of this work was to analyze the interactions among morphological traits of the skull and the brain during late prenatal life (18.5 days postconception) in mice exposed to maternal protein undernutrition. Images from the skull and brain were obtained through micro-computed tomography and 3D landmark coordinates were digitized in order to quantify shape and size of both structures with geometric morphometric techniques. The results highlight a systemic effect of protein restriction on the size of the skull and the brain, which were both significantly reduced in the under-nourished group compared to control group. Skull shape is partially explained by brain size, and patterns of shape variation were only partially coincident with previous re-ports for other ontogenetic stages, suggesting that allomet-ric trajectories across pre- and postnatal ages change their directions. Within the skull, neurocranial and facial shape traits covaried strongly, while subtle covariation was found between the shape of the skull and the brain. These find-ings are in line with former studies in mutant mice and reveal the importance of carrying out analyses of pheno-typic variation in a broad range of developmental stages. The present study contributes to the basic understanding of epigenetic relations among growing tissues and has di-rect implications for the field of paleoanthropology, where inferences about brain morphology are usually derived from skull remains.